Five-quadrant model of unity in diversity of Ibn Khaldun in the context of unity and integration of plural society in Malaysia - Rosfazila Abd Rahman,; Abdul Razif Zaini,; S. Mama, Djhoanna; Munira Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Ibn khaldun is a great sociological scholar and made a great contribution to the world civilization. Whilst national unity and integration are the basic goal of Malaysia in the effort to make Malaysia a strong and united civilization. Unity can ensure national security, economic and political stability. To further strengthen unity between the various ethnicities and races, various strategies have been made through economic, political and educational approaches to achieve the goal of unity. This research aims at describing the situation of Unity and Integration of Plural Society in Malaysia. The research philosophy is mainly positivism. The research technique and strategy are qualitative using content document analysis and narrative in nature. This study is a reflection and extraction of the integrating concepts and frameworks from Khaldunian sociology into modem social science theories for national integration. It started out by defining the different means by which national integration can be achieved such as through the process of assimilation, integration and pluralism. The proposed five quadrant model are explained. This writing has several implications for the situation of unity and integration of the Malaysian plural society which deals with the ethical dilemma of relations between multi-ethnic and multicultural communities. This writing will encourage further strengthen unity and integration and make the community more sensitive to the code of conduct based on Ibn Khaldun’s Five quadrant model of Unity in Diversity in the social set of society. It can be used as a guide to the culture of unity and integration in Malaysia.